We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
140
1
avatar

11/3 - 1/3

 Jun 24, 2019

Best Answer 

 #1
avatar+8810 
+3

11 apples - 1 apple  =  10 apples

 

11 thirds - 1 third  =  10 thirds

 

\(\dfrac{11}{3}\ -\ \dfrac13\ =\ \dfrac{10}{3}\)

.
 Jun 24, 2019
 #1
avatar+8810 
+3
Best Answer

11 apples - 1 apple  =  10 apples

 

11 thirds - 1 third  =  10 thirds

 

\(\dfrac{11}{3}\ -\ \dfrac13\ =\ \dfrac{10}{3}\)

hectictar Jun 24, 2019

4 Online Users